The Effect of Internal Control System, Firm Size, Leverage and Operating Profit on Audit Delay during the Covid-19 Pandemic - Anita Viani; Siti Noor Khikmah; F Farida (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Audit delay is the length or time span of the completion of audit which is measured from the closing date of the financial year to the date of issuance of the audit report. This study aims to examine the factors that affect audit delay which include Internal Control System, firm size, leverage and operating profit. The population of this study are consumer cyclicals sector listed on the IDX for the 2019-2020 period. The sampling technique used in the study used purposive sampling method and the type of data used was secondary data. The selected sample is 78 companies or 156 samples through the specified criteria. Statistical analysis in this study using multiple linear regression. The results of the research show that the Internal Control System and operating profit have a negative effect on audit delay. While the leverage and firm size have no effect on audit delay.